A study on the evolution of voluntary disclosure in corporate annual reports : Singapore evidence. - Aswira A Sat. (2008)
This study examines both cross-sectional variations in voluntary disclosure practices of Singapore companies as well as the evolution of the voluntary disclosures among these companies.